PENGARUH FAKTOR INFLASI, NILAI TUKAR UANG (KURS) RUPIAH, DAN TINGKAT SUKU BUNGA TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) DI BURSA EFEK INDONESIA - Welang, Nehemya; Susilowati, Dwi; Hernadi Moorcy , Nadi (MEDIA RISET EKONOMI [MR.EKO], 2025)
The Composite Stock Price Index (IHSG) is an index that reflects the performance of companies listed on the Indonesia Stock Exchange (IDX). There are many factors that affect the composite stock price index, such as macro and microeconomic factors. The purpose of this study is to determine the economic factors consisting of the inflation rate, the rupiah exchange rate and the interest rate level on the composite stock price index for the 2020-2024 period. The sample used was 60 companies. The data analysis technique used was multiple linear regression with SPSS. The test results show that inflation has a significant effect on the composite stock price index, the rupiah exchange rate does not have a significant effect on the composite stock price index, and the interest rate level has a significant effect on the composite stock price index